Quality and Freshness of Fish available in Super markets of Cochin, India based on Biogenic Amine content - Laly, S. J.; Anupama, T. K.; Ashok Kumar, K.; Sankar, T. V. (Fishery Technology, 2019)
Quality and freshness of thirty nine samples of fresh and frozen fish sold in the super markets of Cochin were determined in terms of biogenic amine content, biochemical and microbial parameters. The contents of putrescine, cadaverin, histamine, agmatine, tyramine, spermine and spermidine were analysed and it showed a wide variation with higher content of spermine and cadaverine. Histamine content was less than 5 mg kg-1 (Range: Nd - 2.19±0.6 mg kg-1). Putrescine, cadaverine, agmatine, tyramine, spermidine and spermine were in the range of Nd – 7.72±1.7 mg kg-1, Nd – 52.8 mg kg-1, Nd – 6.22 mg kg-1, Nd – 4.34 mg kg-1, Nd - 51.8 mg kg-1 and 0.21- 43.95 mg kg-1 respectively. Levels of putrescine and cadaverine were highest in Rastrelliger kanagurta and Lethrinus nebulosus. In the present study 10.3% of samples exceeded Biogenic amine index (BAI) value of 20 mg kg-1. Around 7.7% of samples were having TVBN content more than 30 mg% and 10.3% of samples were having APC greater than or equal to 7 log cfu g-1. As indices based on biogenic amines are not highly correlated with other quality indices, assessment of biogenic amine indices along with other quality indices for fresh fish can be recommended.